Antibacterial Activities of Ni Substituted Ferrite Particles for Biological Applications - Subbiah, Rammohan Chitra; Suruliappan, Subramanian Anjanapriya (Journal of Biotechnology and Biomedical Science, 2022)
In this research work Mg0.45Mn0.55-xNixFe2O4 ferrite particles of varying compositions (x=0.05, x=0.15, x=0.25, x=0.45 and x=0.55) were synthesized using cost effectual co-precipitation route. The synthesized ferrite particles were characterized by collection of techniques. XRD analysis confirmed the formation of cubic spinel structure of the ferrite particles. SEM and AFM analyses illustrated the morphology and size distribution of obtained ferrite particles. FT-IR study exposed that the absence of any additional peak related to second phase. VSM results indicated magnetic analyses such as saturation magnetization (MS), Coercivity (HC) and Remanence (Mr) of ferrite particles. The major objective of the present investigation is to synthesize MgMnNiFe2O4 ferrite particles on cotton fabrics in order to obtain finished fabrics; it is very significant in biological applications. The antibacterial activities of the ferrite particles coated cotton fabrics were tested against selected Gram positive and Gram negative bacteria which showed tremendous results via formation of inhibition zones. The fabricated ferrite particles on cotton fabrics showed great durability evidenced by their antibacterial activities even after 20 washing cycles. Hence, the functionalized cotton fabrics could be used as potential antibacterial agent.
Keywords: ferrite particles; co-precipitation route; magnetic properties; cotton; antibacterial activities; Disc diffusion route.